A nine-pixel matched collimator for low- and medium-energy SPECT imaging. (10th February 2016) - Suzuki, Atsuro; Takeuchi, Wataru; Morimoto, Yuichi; Ueno, Yuichiro; Kobashi, Keiji; Shiga, Tohru; Tamaki, Nagara
Abstract: For low-and medium-energy SPECT imaging without collimator exchange, a wide-aperture parallel-hole collimator—called a 'nine-pixel matched collimator (9-PMC)'—was developed. The hole size of the 9-PMC is matched to nine detector pixels, giving nine (3 × 3) pixels per collimator hole. The 9-PMC was designed to reduce the penetration of medium-energy gamma rays. The performance of the 9-PMC for 99m Tc and 111 In gamma-ray energy was experimentally evaluated and compared with that of a low-energy collimator. A CdTe detector with 1.4 mm pitch was used in conjunction with the 9-PMC. A four-pixel matched collimator ('4-PMC' hereafter) with hole size matched to four detector pixels was also used as a high-sensitivity low-energy collimator. Hole pitch, hole length and septum thickness of the 4-PMC/9-PMC were 2.8/4.2 mm, 26.0/33.4 mm and 0.4/1.0 mm, respectively. The system sensitivities of the 4-PMC and 9-PMC for 99m Tc gamma rays were 221 cps MBq −1 and 211 cps MBq −1, respectively. For the 4-PMC, system sensitivities for 171 and 245 keV 111 In gamma rays were 232 cps MBq −1 and 503 cps MBq −1, respectively, while for the 9-PMC, the system sensitivities for 171 and 245 keV 111 In gamma rays were 145 cps MBq −1 and 106 cps MBq −1, respectively. Spatial resolution of the collimator was analyzed by using modulation transfer functions (MTFs) obtained from the line-source profiles. The results of this analysis demonstrate that the 9-PMC for 99m Tc had frequency ranges for similar (or higher) and lower MTF values compared with those for the 4-PMC, while the 9-PMC for 111 In had higher MTF values than those for the 4-PMC at a wide frequency range. Hot-sphere phantom images showed that the image contrast of the 9-PMC for 99m Tc gamma rays is comparable to that of the 4-PMC, while that of the 9-PMC for 111 In gamma rays is higher than that of the 4-PMC. The developed SPECT with the 9-PMC and CdTe detector provided higher image quality for 111 In gamma rays, or comparable image quality for 99m Tc gamma rays, compared with that of a low-energy collimator.